Penggunaan Media Prezi Pada Proses Pembelajaran Siswa SMA - Susanto, Joko; Haryadi, Joni; Aunnurahman, Aunnurahman; Halida, Halida (Universitas Hamzanwadi, 2023)
The use of innovative and interesting learning media is an important factor in improving student learning outcomes. Prezi is a learning media that can be used to improve student learning outcomes. Prezi offers a unique and dynamic visual approach to presenting information. Prezi allows students to be actively involved in the learning process and improve understanding of concepts. This research aims to examine the potential of Prezi in improving student learning outcomes. This research uses a literature review method by collecting data from published research journals. The research results show that Prezi has the potential to improve student learning outcomes in various subjects. Prezi can improve students' conceptual understanding, critical thinking skills, problem solving skills, creativity and collaboration. Based on the results of this research, it can be concluded that Prezi is a potential learning media for improving student learning outcomes. However, further research needs to be carried out to examine the effectiveness of Prezi in improving student learning outcomes in more depth